Polishing composition, polishing method and method for producing substrate

JP7638667B2Active Publication Date: 2025-03-04FUJIMI INCORPORATED
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2020185763
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-11-20
Filing Date
2020-11-06
Publication Date
2025-03-04
Estimated Expiration
2040-11-06

AI Technical Summary

Benefits of technology

【0025】 本発明に係る研磨組成物は、特定の条件を満たす研磨砥粒および特定の構造を有する添加剤を含み、特定のpHの環境で、酸化物のシリコン含有材料に対する高研磨選択比を実現することができる。より詳細には、本発明にかかる研磨組成物は、シラノール基密度が比較的低い研磨砥粒を使用するため、酸化物の研磨速度を高めることができる。また、本発明にかかる研磨組成物は、特定の構造を有する(つまり、後述の式(I)で示される構造を有する)添加剤分子を使用するため、シリコン含有(例えばシリコンゲルマニウムまたはシリコン)の研磨速度を低減することができるようになる。さらに、本発明にかかる研磨組成物は特定の酸性pH(つまり、pHが1.5以上であって、4.5以下)環境で使用されるため、酸化物の除去速度と酸化物のシリコン含有材料に対する研磨選択比が低下するのを回避できる。本発明にかかる研磨組成物を使用してシリコン含有材料層上に形成された酸化物層に対して化学機械研磨を行う際、研磨停止層としてシリコン含有材料層をそのまま用いることができるため、さらなる研磨停止層(例えば、窒化シリコン層)を形成する必要がない。これにより、プロセスの複雑度をシンプルにできると共に、生産に要される時間とコストを低減することができる。また、本発明にかかる研磨組成物は、添加剤の種類と含量を調整することによって、酸化物の除去速度を調整することができる。例えば、酸化物の除去速度をさらに高めることができ、研磨工程に要される時間が短縮される。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007638667000001
    Figure 0007638667000001
  • Figure 0007638667000002
    Figure 0007638667000002
  • Figure 0007638667000003
    Figure 0007638667000003
Patent Text Reader

Abstract

To provide a polishing composition, a polishing method, and a method for manufacturing a substrate.SOLUTION: A polishing composition comprises polishing abrasive grains, an additive molecule, a pH adjusting agent and a dispersing medium. The polishing abrasive grains contain silica particles, and silanol group density on the silica particle surfaces is 0 to 3.0 / nm2. The silanol group density is calculated and determined on the basis of a specific surface area measured by a BET method and an amount of silanol groups measured by titration. The pH adjusting agent is used to adjust a pH of the polishing composition to a range of 1.5 or more and 4.5 or less. The additive molecule has a structure represented by a formula (I).SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a polishing composition, a polishing method using the polishing composition, and a method for producing a substrate. [Background technology]

[0002] In the semiconductor industry, planarization techniques are generally used to increase the flatness of the surface of a semiconductor substrate (e.g., a wafer). Chemical mechanical polishing (CMP) is one of the commonly used planarization techniques. The chemical mechanical polishing technique includes a method of planarizing the surface of an object to be polished (a polished object) such as a semiconductor substrate by using a polishing composition containing abrasive grains such as silica, alumina, or ceria, an anticorrosive agent, a surfactant, and the like.

[0003] Furthermore, substrates made of semiconductor materials such as silicon or silicon germanium (sometimes abbreviated as "silicon-containing materials" in this specification) are already in widespread use, and thus the need for polishing compositions applicable to polishing substrates made of silicon-containing materials is gradually increasing.

[0004] Patent Document 1 discloses a chemical mechanical polishing composition comprising (A) inorganic particles, organic particles, or a mixture or composite thereof, (B) at least one oxidizing agent, and (C) an aqueous medium. The chemical mechanical polishing composition of Patent Document 1 is applicable to chemical mechanical polishing of elemental germanium or silicon germanium. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Taiwan Patent Application No. 201311842 A1 Specification Summary of the Invention [Problem to be solved by the invention]

[0006] As semiconductor devices become smaller, the requirements for chemical mechanical polishing processes become increasingly severe. For example, semiconductor devices typically use a shallow trench isolation (STI) structure made of oxide (e.g., silicon oxide) to isolate semiconductor elements from one another. In the shallow trench isolation process, chemical mechanical polishing can be performed to remove excess oxide material deposited on the substrate. To stop the chemical mechanical polishing, a polishing stop layer with a relatively low polishing rate is typically formed between the oxide layer and the substrate. To accurately stop the chemical mechanical polishing at a desired position, the polishing selectivity of the oxide layer to the polishing stop layer must be increased. Materials commonly used for the polishing stop layer can include nitrides, carbides, or carbonitrides, such as silicon nitride.

[0007] When forming an oxide layer on a substrate made of silicon-containing material (e.g., silicon germanium substrate or silicon substrate), if the polishing selectivity of the oxide to the substrate material can be increased, it is not necessary to form an additional polishing stop layer (e.g., silicon nitride layer). In this way, the complexity of the process can be simplified and the time and cost required for production can be reduced. In addition, if the polishing rate of the oxide (in this specification, the "polishing rate" is sometimes referred to as the "removal rate") can be increased, the time required for the polishing process can be significantly shortened, and the production efficiency of the product can be improved.

[0008] However, with existing polishing compositions, it remains difficult to sufficiently increase the polishing selectivity (herein, "polishing selectivity" may also be referred to as "polishing rate ratio" or "removal rate ratio") of an oxide to a silicon-containing material (e.g., silicon germanium or silicon). In other words, it remains difficult to use silicon germanium or silicon as a polishing stop layer when performing chemical mechanical polishing on an oxide.

[0009] The present invention has been completed in view of the above-mentioned practical situation, and aims to provide a polishing composition that can increase the polishing rate ratio of oxide to silicon germanium or silicon. Furthermore, the polishing composition provided by the present invention can also increase the polishing rate of oxide. The present invention also provides a polishing method and a method for manufacturing a substrate using such a polishing composition. [Means for solving the problem]

[0010] To achieve the above-mentioned objectives, some embodiments of the present invention provide a polishing composition, a polishing method using the polishing composition, and a method for producing a substrate, as described below.

[0011] [1] The polishing composition is a polishing abrasive containing silica particles, and the silanol group density on the surface of the silica particles is 0 to 3.0 / nm 2 The polishing composition includes abrasive grains, additive molecules, a pH adjuster for adjusting the pH of the polishing composition to a range of 1.5 to 4.5, and a dispersion medium, and the silanol density is calculated based on the specific surface area measured by the BET method and the amount of silanol groups measured by titration. The additive molecules have a structure represented by formula (I).

[0012] [ka]

[0013] In formula (I), R 1 and R 2 are each independently H, C1 to C 18 Straight chain alkyl group, C3-C 18 Branched chain alkyl group or C2-C 18 is a linear alkenyl group; n is an integer of 2 to 40; and m, p, and q are each independently 0 or 1, and r is an integer of 0 to 2, and when m is 1, R 1 is C1~C 18 Straight chain alkyl group, C3-C 18 Branched chain alkyl group or C2-C 18When p is 1, R 2 is C1~C 18 Straight chain alkyl group, C3-C 18 Branched chain alkyl group or C2-C 18 It is a straight-chain alkenyl group.

[0014] [2] In the polishing composition described in [1], the content of the additive molecules is 50 to 10,000 ppm by weight based on the total weight of the polishing composition.

[0015] [3] In the polishing composition according to [1] or [2], the weight-average molecular weight of the additive molecule is 100 to 10,000.

[0016] [4] In the polishing composition according to any one of [1] to [3], in the formula (I), R 1 is H and R 2 C1~C 18 Straight chain alkyl group, C3-C 18 Branched chain alkyl group or C2-C 18 It is a linear alkenyl group; n is an integer of 2 to 20; and m, p, q and r are all 0.

[0017] [5] In the polishing composition according to any one of [1] to [3], in the formula (I), R 1 and R 2 are both H; n is an integer from 2 to 40; and m and p are both 0, and q and r are both 1.

[0018] [6] In the polishing composition according to any one of [1] to [3], in the formula (I), R 1 is C1~C 18 Straight chain alkyl group, C3-C 18 Branched chain alkyl group or C2-C 18 A linear alkenyl group, R 2 is H; n is an integer from 2 to 20; and m and p are both 0, and q and r are both 1.

[0019] [7] In the polishing composition according to any one of [1] to [3], in the formula (I), R 1 is C1~C 18 Straight chain alkyl group, C3-C 18 Branched chain alkyl group or C2-C 18 A linear alkenyl group, R 2 is H; n is an integer from 2 to 20; and m, q and r are all 1, and p is 0.

[0020] [8] In the polishing composition according to any one of [1] to [3], in the formula (I), R 1 and R 2 are all H; n is an integer from 2 to 20; and m, p and q are all 0, and r is 2.

[0021] [9] In the polishing composition according to any one of [1] to [8], the content of the abrasive grains is 0.1 to 10 wt % based on the total weight of the polishing composition.

[0022]

[10] A polishing method includes a step of polishing an object to be polished with the polishing composition according to any one of [1] to [9], wherein the material of the object to be polished includes a silicon-containing material and an oxide, and the silicon-containing material is Si x Ge 1-x where x=0.1 to 1.

[0023]

[11] In the polishing method described in

[10] , when the polishing pressure is 1.0 psi, the polishing composition has a first removal rate R1 for the oxide, the polishing composition has a second removal rate R2 for the silicon-containing material, and the ratio of the first removal rate to the second removal rate R1 / R2 is 10 or greater.

[0024]

[12] A method of manufacturing a substrate includes providing a substrate, a surface of the substrate including a silicon-containing material and an oxide, the silicon-containing material being Si x Ge 1-xand x=0.1 to 1; and polishing the substrate using the polishing composition according to any one of [1] to [9]. Effect of the Invention

[0025] The polishing composition according to the present invention contains polishing grains that satisfy specific conditions and an additive having a specific structure, and can realize a high polishing selectivity of oxide to silicon-containing material in a specific pH environment. More specifically, the polishing composition according to the present invention uses polishing grains with a relatively low silanol group density, and therefore can increase the polishing rate of oxide. In addition, the polishing composition according to the present invention uses an additive molecule having a specific structure (i.e., a structure represented by formula (I) described below), and therefore can reduce the polishing rate of silicon-containing (e.g., silicon germanium or silicon). Furthermore, the polishing composition according to the present invention is used in a specific acidic pH (i.e., pH is 1.5 or more and 4.5 or less) environment, and therefore it is possible to avoid a decrease in the removal rate of oxide and the polishing selectivity of oxide to silicon-containing material. When chemical mechanical polishing is performed on an oxide layer formed on a silicon-containing material layer using the polishing composition according to the present invention, the silicon-containing material layer can be used as it is as a polishing stop layer, and therefore there is no need to form an additional polishing stop layer (e.g., a silicon nitride layer). This can simplify the complexity of the process and reduce the time and cost required for production. In addition, the polishing composition according to the present invention can adjust the oxide removal rate by adjusting the type and content of additives, for example, the oxide removal rate can be further increased and the time required for the polishing process can be shortened. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0026] In order to make the above and other objects, features and advantages of the present invention more clear and understandable, preferred embodiments are given below and described in detail.

[0027] The following describes embodiments of the present invention, but the present invention is not limited to these embodiments.

[0028] One embodiment of the present invention is a polishing abrasive containing silica particles, and the silanol group density on the surface of the silica particles is 0 to 3.0 / nm 2 The polishing composition includes abrasive grains, additive molecules, a pH adjuster for adjusting the pH of the polishing composition to a range of 1.5 to 4.5, and a dispersion medium, and the silanol density is calculated based on the specific surface area measured by the BET method and the amount of silanol groups measured by titration. The additive molecules have a structure represented by formula (I).

[0029] [ka]

[0030] In formula (I), R 1 and R 2 are each independently H, C1 to C 18 Straight chain alkyl group, C3-C 18 Branched chain alkyl group or C2-C 18 is a linear alkenyl group; n is an integer of 2 to 40; and m, p, and q are each independently 0 or 1, and r is an integer of 0 to 2, and when m is 1, R 1 is C1~C 18 Straight chain alkyl group, C3-C 18 Branched chain alkyl group or C2-C 18 When p is 1, R 2 is C1~C 18 Straight chain alkyl group, C3-C 18 Branched chain alkyl group or C2-C 18 It is a straight-chain alkenyl group.

[0031] In this embodiment, the polishing composition uses silica particles with a relatively low silanol group density as a polishing abrasive and is made by combining additives having a specific structure, and can realize a high polishing selectivity of oxide to silicon germanium or silicon (i.e., a high polishing selectivity of oxide / silicon-containing material) in a specific pH environment. When the polishing composition of this embodiment is used to perform chemical mechanical polishing on a polishing object containing a silicon-containing material and an oxide, the removal rate of the oxide can be increased and the polishing selectivity of the oxide to silicon germanium or silicon can be increased. Therefore, the silicon-containing material can be used as a polishing stop layer, and there is no need to form an additional polishing stop layer. This improves the surface flatness of the polishing object, simplifies the process complexity, and reduces the time and cost required for production.

[0032] There is no particular limitation on the object to be polished that can be applied to the polishing composition of the present invention, and any general semiconductor substrate can be used. The polishing composition of the present invention is particularly suitable for polishing a substrate containing a silicon-containing material and an oxide on the surface, and the technical effect of the present invention can be fully exerted. A specific example of the oxide is silicon oxide. The silicon-containing material can include, for example, amorphous silicon, single crystal silicon, polycrystalline silicon, silicon germanium, or a combination thereof. A specific example of the silicon-containing material is, for example, a silicon-containing material having the molecular formula Si x Ge 1-x Examples of the silicon-containing material include those represented by the following formula: The value of x in the above molecular formula is preferably 0.1 or more, more preferably 0.2 or more, and even more preferably 0.3 or more. The value of x in the above molecular formula is preferably 1 or less, more preferably 0.9 or less, and even more preferably 0.8 or less.

[0033] Furthermore, in this specification, the "substrate containing a silicon-containing material and an oxide" may be a substrate containing a silicon-containing material and an oxide on the surface thereof, and there is no particular limitation on the embodiment. For example, a patterned structure formed of an oxide and a silicon-containing material may be present on the surface of any substrate, an oxide layer may be present on a substrate made of a silicon-containing material, or a patterned structure formed of an oxide layer and other materials may be present on a substrate (or a silicon-containing material layer) made of a silicon-containing material. Although several different embodiments of the "substrate containing a silicon-containing material and an oxide" are given here, they are not intended to limit the present invention. The present invention may include other possible embodiments of any "substrate containing a silicon-containing material and an oxide".

[0034] Various components contained in the polishing composition according to this embodiment will be described below.

[0035] [Abrasive grains] The polishing composition of the present embodiment contains silica as the polishing abrasive. In some embodiments of the present invention, the polishing abrasive is colloidal silica. In some embodiments of the present invention, silica particles having a relatively low silanol group density are used as the polishing abrasive. In this specification, the term "silanol group density" refers to the number of silanol groups per unit area of ​​the silica particle surface. The silanol group density is an index for expressing the electrical or chemical properties of the silica particle surface.

[0036] In this specification, the silanol density is calculated based on the specific surface area measured by the BET method and the amount of silanol groups measured by titration. For example, the average silanol group density (unit: silanol / nm2) on the surface of silica (polishing grains) was determined by the Sears titration method using neutralization titration described in "Analytical Chemistry, vol. 28, No. 12, 1956, 1982-1983" by GW Sears. 2) can be calculated. The "Sears titration method" is an analytical method commonly used by colloidal silica manufacturers to evaluate silanol group density, and is a calculation based on the amount of sodium hydroxide solution required to change the pH from 4 to 9. Details of silanol density measurement are described in detail in the Examples below.

[0037] The silanol group density of the polishing grains is 0 to 3.0 / nm 2 When the silanol group density is within the above range, the silica particles can well adsorb the additive molecules in this embodiment. This allows the additive molecules to be adsorbed and concentrated on the surface of the polishing abrasive grains, which in turn makes it possible to avoid aggregation of the polishing abrasive grains due to steric hindrance of the additive molecules. This improves the dispersion stability of the polishing abrasive grains in the polishing composition, makes the polishing abrasive grains less likely to aggregate, and improves storage stability. On the other hand, by adsorbing and concentrating the additive molecules on the surface of the polishing abrasive grains, the polishing selectivity of the oxide to silicon germanium or silicon can be improved. The silanol group density of the polishing abrasive grains is 0 / nm 2 More than 0.5 particles / nm is preferable. 2 More preferably, 1.0 particles / nm 2 More preferably, 1.2 particles / nm 2 The above is even more preferable. The silanol group density of the polishing grains is 2.5 / nm 2 Less than 2.0 particles / nm is preferable. 2 Less than 1.8 particles / nm is more preferable. 2 The following is even more preferred:

[0038] In one embodiment of the present invention, the number of silanol groups per unit surface area of ​​the abrasive grains is 0 to 3.0 / nm 2 To achieve this, the abrasive grain size can be controlled by selecting a manufacturing method for the abrasive grains, and it is preferable to carry out a heat treatment such as calcination. In one embodiment of the present invention, calcination is carried out, for example, by holding the abrasive grains (e.g., silica) in an environment of 120 to 200°C for 30 minutes or more. By carrying out such a heat treatment, the number of silanol groups on the abrasive grain surface can be reduced to 0 to 3.0 groups / nm. 2Unless such special treatment is performed, the number of silanol groups on the abrasive grain surface is 0 / nm2. 2 More than 3.0 pieces / nm 2 It cannot be less than this.

[0039] The average primary particle size of the polishing grains is preferably 5 nm or more, more preferably 7 nm or more, even more preferably 10 nm or more, and particularly preferably 25 nm or more. As the average primary particle size of the polishing grains increases, the polishing rate for silicon-containing materials and oxides can be increased. The average primary particle size of the polishing grains is preferably 120 nm or less, more preferably 80 nm or less, and even more preferably 50 nm or less. As the average primary particle size of the polishing grains decreases, a polished surface with fewer scratches can be easily obtained when polishing an object to be polished using the polishing composition. In addition, the value of the average primary particle size of the polishing grains can be calculated based on the specific surface area measured using the BET method.

[0040] The average secondary particle diameter of the polishing abrasive grains is preferably 10 nm or more, more preferably 20 nm or more, even more preferably 30 nm or more, and particularly preferably 50 nm or more. As the average secondary particle diameter of the polishing abrasive grains increases, the polishing speed for silicon-containing materials and oxides can be increased. The average secondary particle diameter of the polishing abrasive grains is preferably 250 nm or less, more preferably 200 nm or less, even more preferably 150 nm or less, and particularly preferably 100 nm or less. As the average secondary particle diameter of the polishing abrasive grains decreases, a polished surface with fewer scratches can be easily obtained when polishing an object to be polished using the polishing composition. In addition, the value of the average secondary particle diameter of the polishing abrasive grains can be measured, for example, by a laser light scattering method.

[0041] In some embodiments of the present invention, the zeta potential of the polishing grains under acidic conditions is positive, so that the polishing grains can be strongly repelled from each other and dispersed well. Therefore, the storage stability of the polishing composition is improved. Furthermore, in some embodiments of the present invention, the surface zeta potential of the polishing grains is positive, so that there is an electrostatic attraction between the polishing grains and the negatively charged object to be polished (e.g., oxides), and therefore the polishing rate of the oxides can be increased. In some embodiments of the present invention, the zeta potential of the polishing grains under specific acidic conditions (e.g., pH 1.5 or more and 4.5 or less) is preferably +10 mV or more, more preferably +20 mV or more, and even more preferably +30 mV or more. In addition, the zeta potential of the polishing grains under specific acidic conditions (e.g., pH 1.5 or more and 4.5 or less) is preferably +100 mV or less, more preferably +80 mV or less; more preferably +60 mV or less, and particularly preferably +40 mV or less.

[0042] In some embodiments of the present invention, the content of the abrasive grains is preferably 0.01% by weight or more, more preferably 0.05% by weight or more, even more preferably 0.1% by weight or more, and particularly preferably 0.3% by weight or more, based on the total weight of the polishing composition. The content of the abrasive grains is preferably 10.0% by weight or less, more preferably 5.0% by weight or less, even more preferably 2.0% by weight or less, and particularly preferably 1.0% by weight or less. The higher the content of the abrasive grains, the higher the polishing speed of the object to be polished. On the other hand, the lower the content of the abrasive grains, the lower the material cost of the polishing composition and the less likely the agglomeration of the abrasive grains will occur. Furthermore, by reducing the content of the abrasive grains, it is possible to avoid the surface of the object to be polished from becoming uneven due to excessive polishing.

[0043] [Additive molecules] The polishing composition of this embodiment includes at least one additive molecule, and the additive molecule has a structure represented by formula (I):

[0044] [ka]

[0045] In formula (I), R 1 and R 2 are each independently H, C1 to C 18 Straight chain alkyl group, C3-C 18 Branched chain alkyl group or C2-C 18 is a linear alkenyl group; n is an integer of 2 to 40; and m, p, and q are each independently 0 or 1, and r is an integer of 0 to 2, and when m is 1, R 1 is C1~C 18 Straight chain alkyl group, C3-C 18 Branched chain alkyl group or C2-C 18 When p is 1, R 2 is C1~C 18 Straight chain alkyl group, C3-C 18 Branched chain alkyl group or C2-C 18 In one embodiment, when m is 1, R 1 is C1~C 18 Straight chain alkyl group, C3-C 18 Branched chain alkyl group or C2-C 18 When p is 1, R 2 is C1~C 18 Straight chain alkyl group, C3-C 18 Branched chain alkyl group or C2-C 18 It is a straight-chain alkenyl group.

[0046] Here, in this specification, C1 to C 18 Straight-chain alkyl groups (i.e., straight-chain alkyl groups having 1 to 18 carbon atoms) or C3 to C 18The branched alkyl group (i.e., a branched alkyl group having 3 to 18 carbon atoms) is not particularly limited, and examples thereof include an n-propyl group, an isopropyl group, an n-butyl group, an isobutyl group, a sec-butyl group, a tert-butyl group, an n-pentyl group, an isopentyl group, a 2-methylbutyl group, a sec-pentyl group, a neopentyl group, a 1,2-dimethylpropyl group, a tert-pentyl group, a hexyl group, an isohexyl group, a heptyl group, an octyl group, a nonyl group, a decyl group, an undecyl group, a dodecyl group (auryl group), a 2-ethylhexyl group, a tridecyl group, a tetradecyl group, a pentadecyl group, a hexadecyl group, a heptadecyl group, and an octadecyl group.

[0047] In this specification, C2 to C 18 Straight-chain alkenyl groups (straight-chain alkenyl groups having 2 to 20 carbon atoms are not particularly limited, and examples thereof include ethenyl groups, propenyl groups, allyl groups, isopropenyl groups, 1-hexenyl groups, 2-hexenyl groups, 3-hexenyl groups, 1-heptenyl groups, 2-heptenyl groups, 3-heptenyl groups, 9-decenyl groups, 11-dodecenyl groups, (Z)-9-pentadecenyl groups, and oleyl groups (Z-9-octadecenyl groups).

[0048] As mentioned above, the silanol group density on the surface of the silica polishing grains is relatively low, so the hydrophobicity of the polishing grains is increased. In addition, the surface of the silicon-containing material (e.g., silicon germanium or silicon) to be polished is also relatively highly hydrophobic. When the above-mentioned additive is not used, the affinity between the hydrophobic polishing grains and the hydrophobic silicon-containing material is relatively large, so that the polishing rate of the polishing grains to the silicon-containing material is high. In such a case, the polishing rate ratio of the oxide to the silicon-containing material is too low, so that the silicon-containing material cannot be used as a polishing stop layer when polishing the oxide.

[0049] See the structure shown in formula (I) above. The additive molecule comprises a hydrophobic chain segment, e.g., R 1 , R 2or alkyl chain segments on the backbone. The additive molecules are adsorbed and concentrated on the hydrophobic surface of the polishing grains and the silicon-containing material through the hydrophobic molecular chain segments. Thus, a thin layer of additive molecules is adsorbed on the surface of the polishing grains and the silicon-containing material. The three-dimensional structure of the additive molecules creates obstacles, which can reduce or avoid direct contact between the polishing grains and the silicon-containing material. In other words, the additive molecules can form a structure similar to a protective layer on the surface of the silicon-containing material, which can greatly reduce the polishing rate of the silicon-containing material. This increases the polishing rate ratio of the oxide to the silicon-containing material, which allows the silicon-containing material to be used as a polishing stop layer during oxide polishing.

[0050] Also, please refer to the structure shown in formula (I) above. The additive molecule has a hydrophilic group, such as a hydroxyl (-OH) group, at the terminal position. Therefore, after the additive molecule is adsorbed on the surface of the polishing abrasive grain, the hydrophilic group on the surface of the polishing abrasive grain increases, and the hydrophilicity of the polishing abrasive grain increases accordingly. Furthermore, the surface of the oxide of the object to be polished is also a surface with relatively high hydrophilicity. Although a thin layer formed by the additive molecule is adsorbed on the surface of the polishing abrasive grain, the affinity between the hydrophilic polishing abrasive grain and the hydrophilic oxide is sufficiently large, and in addition, there is an electrostatic attraction between the polishing abrasive grain and the oxide, so that the polishing rate of the oxide can still be moderately increased. This further increases the polishing rate ratio of the oxide to the silicon-containing material, making it more advantageous to use the silicon-containing material as a polishing stop layer when polishing the oxide. In addition, the increase in the polishing rate of the oxide also leads to a reduction in the time required for the polishing process, contributing to an improvement in production efficiency.

[0051] In some embodiments of the present invention, in the structure of formula (I), R 1 is H and R 2 C1~C 18 Straight chain alkyl group, C3-C 18 Branched chain alkyl group or C2-C 18is a linear alkenyl group; n is an integer between 2 and 20; and m, p, q, and r are all 0. In such an embodiment, the molecular structure of the additive molecule is relatively simple and easily arranged closely. Therefore, the additive molecule is likely to form a thin layer with a relatively dense structure on the surface of the polishing grain and the silicon-containing material, and thus can protect the silicon-containing material well. Therefore, the polishing rate of the silicon-containing material can be significantly reduced. Furthermore, in such an embodiment, the additive molecule has a large amount of hydrophilic groups, so that the hydrophilicity of the polishing grain surface can be increased. Therefore, the affinity between the polishing grain and the hydrophilic oxide is increased, and thus the polishing rate of the oxide is further increased. This further increases the polishing rate ratio of the oxide to the silicon-containing material, making it more advantageous to use the silicon-containing material as a polishing stop layer when polishing the oxide, and also leads to a reduction in the time required for the polishing process.

[0052] In this embodiment, R 2 is preferably C1 to C 18 A straight chain alkyl group, preferably C1 to C 10 It is a straight-chain alkyl group, more preferably a C1 to C5 straight-chain alkyl group, and even more preferably a C1 to C3 straight-chain alkyl group.

[0053] In some embodiments of the present invention, in the structure of formula (I), R 1 and R 2are both H; n is an integer between 2 and 40; and m and p are both 0, and q and r are both 1. In such an embodiment, the molecular structure of the additive molecule is relatively simple and easily arranged closely. Therefore, the additive molecule is likely to form a thin layer with a relatively dense structure on the surface of the polishing grain and the silicon-containing material, and thus can protect the silicon-containing material well. Therefore, the polishing rate of the silicon-containing material can be significantly reduced. Furthermore, in such an embodiment, the additive molecule has a large amount of hydrophilic groups, so that the hydrophilicity of the polishing grain surface can be increased. Therefore, the affinity between the polishing grain and the hydrophilic oxide is increased, and thus the polishing rate of the oxide is further increased. This further increases the polishing rate ratio of the oxide to the silicon-containing material, making it more advantageous to use the silicon-containing material as a polishing stop layer when polishing the oxide, and also leads to a reduction in the time required for the polishing process.

[0054] In some embodiments of the present invention, in the structure of formula (I), R 1 and R 2 is H; and m, p and q are all 0, and r is 2. In such an embodiment, the molecular structure of the additive molecule is relatively simple and easily arranged closely. Therefore, the additive molecule is easily formed on the surface of the polishing grain and the silicon-containing material with a relatively dense thin layer, and thus can protect the silicon-containing material well. Therefore, the polishing rate of the silicon-containing material can be significantly reduced. Furthermore, in such an embodiment, the additive molecule has a large amount of hydrophilic groups, so that the hydrophilicity of the polishing grain surface can be increased. Therefore, the affinity between the polishing grain and the hydrophilic oxide is increased, and thus the polishing rate of the oxide is further increased. This further increases the polishing rate ratio of the oxide to the silicon-containing material, which is more advantageous for using the silicon-containing material as a polishing stop layer when polishing the oxide, and also leads to a reduction in the time required for the polishing process.

[0055] In some embodiments of the present invention, in the structure shown in formula (I), R 1 is C1~C 18Straight chain alkyl group, C3-C 18 Branched chain alkyl group or C2-C 18 A linear alkenyl group, R 2 is H; n is an integer between 2 and 20; and m and p are both 0, and q and r are both 1. In such an embodiment, the additive molecule has a hydrophobic molecular chain segment (i.e., an alkyl chain segment located at the end). Thus, the additive molecule can be more easily adsorbed to the hydrophobic surface of the polishing grains and the silicon-containing material. Furthermore, the hydrophobic molecular chain segment can change the three-dimensional structure of the additive molecule to a larger one, which is advantageous for further reducing or avoiding direct contact between the polishing grains and the silicon-containing material. This further reduces the polishing rate of the silicon-containing material and further increases the polishing rate ratio of the oxide to the silicon-containing material, making it more advantageous to use the silicon-containing material as a polishing stop layer when polishing the oxide.

[0056] In this embodiment, R 1 is preferably C3 to C 18 Straight chain alkyl group or C2-C 18 A linear alkenyl group, more preferably a C5-C 18 Straight chain alkyl group or C5-C 18 A linear alkenyl group, more preferably C 10 ~C 18 Linear alkyl group or C 10 ~C 18 A linear alkenyl group, even more preferably C 10 ~C 16 Linear alkyl group or C 12 ~C 18 A linear alkenyl group, particularly preferably C 10 ~C 14 It is a straight chain alkyl group.

[0057] In some embodiments of the present invention, in the structure shown in formula (I), R 1 is H and R 2 is C1~C 18 Straight chain alkyl group, C3-C 18Branched chain alkyl group or C2-C 18 is a linear alkenyl group; n is an integer between 2 and 20; and m and p are both 0, and q and r are both 1. In such an embodiment, the additive molecule has a large amount of hydrophobic molecular chain segments (i.e., alkyl chain segments located in the side chains). Thus, the additive molecule can be more easily adsorbed on the hydrophobic surface of the polishing grains and the silicon-containing material. In addition, the large amount of hydrophobic molecular chain segments can change the three-dimensional structure of the additive molecule to a larger one, which is advantageous for further reducing or avoiding direct contact between the polishing grains and the silicon-containing material. This further reduces the polishing rate of the silicon-containing material and further increases the polishing rate ratio of the oxide to the silicon-containing material, making it more advantageous to use the silicon-containing material as a polishing stop layer when polishing the oxide.

[0058] In this embodiment, R 2 is preferably C3 to C 18 Straight chain alkyl group or C2-C 18 A linear alkenyl group, more preferably a C5-C 18 Straight chain alkyl group or C5-C 18 A linear alkenyl group, more preferably C 10 ~C 18 Linear alkyl group or C 10 ~C 18 A linear alkenyl group, even more preferably C 10 ~C 16 Linear alkyl group or C 12 ~C 18 A linear alkenyl group, particularly preferably C 10 ~C 14 It is a straight chain alkyl group.

[0059] In some embodiments of the present invention, in the structure shown in formula (I), R 1 is C1~C 18 Straight chain alkyl group, C3-C 18 Branched chain alkyl group or C2-C 18 A linear alkenyl group, R 2is H; n is an integer between 2 and 20; and m, q and r are all 1, and p is 0. In such an embodiment, the additive molecule has a hydrophobic molecular chain segment (i.e., an alkyl chain segment located at the end). Thus, the additive molecule can be more easily adsorbed to the hydrophobic surface of the polishing grains and the silicon-containing material. Furthermore, the hydrophobic molecular chain segment can change the three-dimensional structure of the additive molecule to a larger one, which is advantageous for further reducing or avoiding direct contact between the polishing grains and the silicon-containing material. This further reduces the polishing rate of the silicon-containing material and further increases the polishing rate ratio of the oxide to the silicon-containing material, making it more advantageous to use the silicon-containing material as a polishing stop layer when polishing the oxide.

[0060] In this embodiment, R 1 is preferably C3 to C 18 Straight chain alkyl group or C2-C 18 A linear alkenyl group, more preferably a C5-C 18 Straight chain alkyl group or C5-C 18 A linear alkenyl group, more preferably C 10 ~C 18 Linear alkyl group or C 10 ~C 18 A linear alkenyl group, even more preferably C 10 ~C 16 Linear alkyl group or C 12 ~C 18 A linear alkenyl group, particularly preferably C 10 ~C 14 It is a straight chain alkyl group.

[0061] In some embodiments of the present invention, in the structure shown in formula (I), R 1 is H and R 2 is C1~C 18 Straight chain alkyl group, C3-C 18 Branched chain alkyl group or C2-C 18is a linear alkenyl group; n is an integer between 2 and 20; and m is 0, and p, q and r are all 1. In such an embodiment, the additive molecule has a large amount of hydrophobic molecular chain segments (i.e., alkyl chain segments located in the side chains). Thus, the additive molecule can be more easily adsorbed on the hydrophobic surface of the polishing grains and the silicon-containing material. In addition, the large amount of hydrophobic molecular chain segments can change the three-dimensional structure of the additive molecule to a larger one, which is advantageous for further reducing or avoiding direct contact between the polishing grains and the silicon-containing material. This further reduces the polishing rate of the silicon-containing material and further increases the polishing rate ratio of the oxide to the silicon-containing material, making it more advantageous to use the silicon-containing material as a polishing stop layer when polishing the oxide.

[0062] In this embodiment, R 2 is preferably C3 to C 18 Straight chain alkyl group or C2-C 18 A linear alkenyl group, more preferably a C5-C 18 Straight chain alkyl group or C5-C 18 A linear alkenyl group, more preferably C 10 ~C 18 Linear alkyl group or C 10 ~C 18 A linear alkenyl group, even more preferably C 10 ~C 16 Linear alkyl group or C 12 ~C 18 A linear alkenyl group, particularly preferably C 10 ~C 14 It is a straight chain alkyl group.

[0063] In some embodiments of the present invention, the weight average molecular weight (MW) of the additive molecule is preferably 100 or more, more preferably 200 or more, and even more preferably 300 or more. In addition, the weight average molecular weight (MW) of the additive molecule is preferably 10,000 or less, more preferably 6,000 or less, and even more preferably 4,000 or less. The weight average molecular weight in this specification is measured by gel permeation chromatography (GPC) using polystyrene as a standard.

[0064] In some embodiments of the invention, the weight average molecular weight (MW) of the additive molecules is 100 or more, 200 or more, 250 or more, 300 or more, 450 or more, 400 or more, 500 or more, or 600 or more. Also, in some embodiments of the invention, the weight average molecular weight (MW) of the additive molecules is 1500 or less, 1000 or less, 950 or less, 900 or less, 800 or less, 700 or less, 650 or less, or 600 or less.

[0065] In some embodiments of the present invention, in formula (I), R 1 is H and R 2 C1~C 18 Straight chain alkyl group, C3-C 18 Branched chain alkyl group or C2-C 18 is a linear alkenyl group; n is an integer from 2 to 20; and m, p, q, and r are all 0, the weight average molecular weight (MW) of the additive molecule is 100 or more, 200 or more, 250 or more, 300 or more, or 400 or more. 1 is H and R 2 C1~C 18 Straight chain alkyl group, C3-C 18 Branched chain alkyl group or C2-C 18 When it is a linear alkenyl group; n is an integer from 2 to 20; and m, p, q, and r are all 0, the weight average molecular weight (MW) of the additive molecule is 1000 or less, 950 or less, 900 or less, 800 or less, 700 or less, 600 or less, or 500 or less.

[0066] In some embodiments of the present invention, in formula (I), R 1 and R 2 are both H; n is an integer from 2 to 40; and m and p are both 0 and q and r are both 1, the weight average molecular weight (MW) of the additive molecule is 100 or more, 150 or more, 200 or more, 250 or more, 280 or more, 300 or more, 400 or more, 500 or more, 600 or more, or 700 or more. In some embodiments of the present invention, in formula (I), R 1 and R 2 are both H; n is an integer from 2 to 40; and m and p are both 0, and q and r are both 1, then the weight average molecular weight (MW) of the additive molecules is 3000 or less, 1500 or less, 1000 or less, 900 or less, or 800 or less.

[0067] In some embodiments of the present invention, when the hydrophobic molecular chain segment has an alkyl ether, that is, in formula (I), (i) R 1 is H and R 2 is C1~C 18 Straight chain alkyl group, C3-C 18 Branched chain alkyl group or C2-C 18 is a linear alkenyl group; n is an integer from 2 to 20; and m and p are both 0, and q and r are both 1; and (ii) R 1 is C1~C 18 Straight chain alkyl group, C3-C 18 Branched chain alkyl group or C2-C 18 A linear alkenyl group, R 2 is H; n is an integer from 2 to 20; and m and p are both 0, and q and r are both 1, the weight average molecular weight (MW) of the additive molecule is 100 or more, 200 or more, 250 or more, 300 or more, 350 or more, or 400 or more. In some embodiments of the present invention, when the additive molecule has an alkyl ether as the hydrophobic molecular chain segment, the weight average molecular weight (MW) of the additive molecule is 1500 or less, 1000 or less, 900 or less, 800 or less, 600 or less, or 500 or less.

[0068] In some embodiments of the present invention, when the hydrophobic molecular chain segment has a fatty acid ester, that is, in formula (I), (i) R 1 is H and R 2 is C1~C 18 Straight chain alkyl group, C3-C 18 Branched chain alkyl group or C2-C 18 is a linear alkenyl group; n is an integer from 2 to 20; and m is 0, and p, q, and r are all 1; and (ii) R 1 is C1~C 18 Straight chain alkyl group, C3-C 18 Branched chain alkyl group or C2-C 18 A linear alkenyl group, R 2 is H; n is an integer of 2 to 20; and m, q, and r are all 1, and p is 0, the weight average molecular weight (MW) of the additive molecule is 100 or more, 200 or more, 250 or more, 300 or more, 350 or more, or 400 or more. In some embodiments of the present invention, when the additive molecule has a fatty acid ester as the hydrophobic molecular chain segment, the weight average molecular weight (MW) of the additive molecule is 1500 or less, 1000 or less, 900 or less, 800 or less, 700 or less, or 600 or less.

[0069] In some embodiments of the present invention, in formula (I), R 1 and R 2 are all H; n is an integer from 2 to 20; and m, p, and q are all 0 and r is 2, the weight average molecular weight (MW) of the additive molecule is 100 or more, 150 or more, 200 or more, 220 or more, or 230 or more. In some embodiments of the present invention, in formula (I), R 1 and R 2 are all H; n is an integer from 2 to 20; and m, p, and q are all 0, and r is 2, then the weight average molecular weight (MW) of the additive molecules is 1000 or less, 800 or less, 600 or less, 500 or less, or 400 or less.

[0070] If the weight average molecular weight of the additive molecule is too large, the three-dimensional structure of the additive molecule may become too large. In such a case, gaps are easily formed between the additive molecules adsorbed on the polishing grains and the silicon-containing material, and it is difficult to form a thin layer with a dense structure on the surface of the polishing grains and the silicon-containing material. As a result, the additive molecule cannot protect the silicon-containing material well, and the polishing rate of the silicon-containing material cannot be sufficiently reduced. Therefore, the polishing rate ratio of the oxide to the silicon-containing material cannot be increased, which is disadvantageous for using the silicon-containing material as a polishing stop layer when polishing the oxide.

[0071] On the other hand, if the weight average molecular weight of the additive molecule is too small, the additive molecule may have too few hydrophobic chain segments and too high hydrophilicity. In such a case, the additive molecule may be difficult to adsorb to the surface of the polishing grain and the silicon-containing material. Therefore, the additive molecule cannot protect the silicon-containing material well and cannot sufficiently reduce the polishing rate of the silicon-containing material. Furthermore, if the additive molecule is too hydrophilic, a thin layer formed by the additive molecule may be adsorbed on the hydrophilic oxide surface, so the polishing rate of the oxide may decrease. Therefore, the polishing rate ratio of the oxide to the silicon-containing material is low, which is unfavorable for using the silicon-containing material as a polishing stop layer when polishing the oxide.

[0072] The weight average molecular weight of the additive molecule can be a value measured by the GPC method (water-based, polyethylene oxide equivalent). The weight average molecular weight can be determined by gel permeation chromatography (GPC) using a GPC device (Shimadzu Corporation, model: Prominence + ELSD detector (ELSD-LTII)) or the like in terms of polyethylene glycol.

[0073] The additive molecules may be commercially available products or synthetic products. When they are synthesized, the production method is not particularly limited, and known production methods can be used.

[0074] In some embodiments of the present invention, the content of the additive molecules is preferably 10 ppm by weight or more, more preferably 30 ppm by weight or more, even more preferably 50 ppm by weight or more, and particularly preferably 70 ppm by weight or more, based on the total weight of the polishing composition. The content of the additive molecules is preferably 10,000 ppm by weight or less, more preferably 5,000 ppm by weight or less, preferably 2,000 ppm by weight or less, and particularly preferably 1,000 ppm by weight or less.

[0075] In some embodiments of the present invention, the content of the additive molecules is 60 ppm or more, 80 ppm or more, 90 ppm or more, 95 ppm or more, 120 ppm or more, 150 ppm or more, or 200 ppm or more by weight based on the total weight of the polishing composition, and in some embodiments of the present invention, the content of the additive molecules is 900 ppm or less, 700 ppm or less, 500 ppm or less, 400 ppm or less, 350 ppm or less, or 300 ppm or less by weight based on the total weight of the polishing composition.

[0076] If the content of additive molecules in the polishing composition is too high, too many additive molecules may be adsorbed on the surface of polishing grains and silicon-containing material.If the content of additive molecules is too high, additive molecules may also form a thin layer on the surface of oxide.This causes both the polishing speed of silicon-containing material and the polishing speed of oxide to decrease, and the polishing speed ratio of oxide to silicon-containing material cannot be sufficiently increased, which is disadvantageous for using silicon-containing material as polishing stop layer when polishing oxide, and is also disadvantageous for shortening the time required for polishing process.

[0077] On the other hand, if the content of additive molecules in the polishing composition is too low, it is difficult for the additive molecules to form a thin layer on the surface of the polishing grains and the silicon-containing material, especially, it is difficult to cover the entire surface of the polishing grains and the silicon-containing material. Therefore, the additive molecules cannot protect the silicon-containing material well, and the polishing speed of the silicon-containing material cannot be sufficiently reduced. In addition, if the content of additive molecules is too low, the hydrophilicity of the polishing grains is insufficient, and it is difficult to effectively increase the affinity between the polishing grains and the hydrophilic oxide, so that the polishing speed of the oxide cannot be increased. As mentioned above, if the content of additive molecules is too low, it is difficult to increase the polishing speed ratio of the oxide to the silicon-containing material. Therefore, it is disadvantageous to use the silicon-containing material as a polishing stop layer when polishing the oxide.

[0078] [pH adjuster] The polishing composition of the present embodiment contains a pH adjuster. The pH value of the polishing composition can be adjusted to a range of 1.5 to 4.5 by the pH adjuster. Known acids or bases can be used as the pH adjuster.

[0079] The acid of the pH adjuster used in the polishing composition of this embodiment may be an inorganic acid or an organic acid, or may be a chelating agent.Specific examples of inorganic acids that can be used as pH adjusters include hydrochloric acid (HCl), sulfuric acid (H2SO4), nitric acid (HNO3), hydrofluoric acid (HF), boric acid (H3BO3), carbonic acid (H2CO3), hypophosphorous acid (H3PO2), phosphorous acid (H3PO3) and phosphoric acid (H3PO4).Of these inorganic acids, hydrochloric acid, sulfuric acid, nitric acid and phosphoric acid are preferred.

[0080] Specific examples of organic acids that can be used as pH adjusters include formic acid, acetic acid, propionic acid, butyric acid, valeric acid, 2-methylbutyric acid, n-hexanoic acid, 3,3-dimethylbutyric acid, 2-ethylbutyric acid, 4-methylpentanoic acid, n-heptanoic acid, 2-methylhexanoic acid, n-octanoic acid, 2-ethylhexanoic acid, benzoic acid, hydroxyacetic acid, salicylic acid, glyceric acid, oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, maleic acid, phthalic acid, malic acid, tartaric acid, citric acid, lactic acid, glyoxylic acid, and the like. Examples of suitable organic acids include 2-furan carboxylic acid, 2,5-furandicarboxylic acid, 3-furan carboxylic acid, 2-tetrahydrofuran carboxylic acid, methoxyacetic acid, methoxyphenylacetic acid, and phenoxyacetic acid. Organic sulfuric acids such as methanesulfonic acid, ethanesulfonic acid, and 2-hydroxyethanesulfonic acid may also be used. Among these organic acids, preferred are oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, maleic acid, phthalic acid, malic acid, tartaric acid, 2,5-furandicarboxylic acid, and citric acid.

[0081] The base of the pH adjuster used in the polishing composition of this embodiment may include an alkali metal hydroxide or its salt, a Group II element hydroxide or its salt, a quaternary ammonium hydroxide or its salt, ammonia, and an amine. Specific examples of the alkali metal include potassium and sodium.

[0082] As the pH of the polishing composition increases, the zeta potential of the polishing grain surface shifts to a negative value, and the zeta potential of the oxide and silicon-containing material surfaces also shift to a negative value. Therefore, if the pH of the polishing composition is too high (for example, pH 5 or higher), the zeta potential of the polishing grain surface may become negative, and the zeta potential of the polishing object surface may also become negative. Therefore, the electrostatic repulsion between the polishing grain and the polishing object (including the oxide and silicon-containing material) increases, and the polishing rates of both the silicon-containing material and the oxide are significantly reduced, making it difficult to increase the polishing rate ratio of the oxide to the silicon-containing material. Therefore, it is disadvantageous to use the silicon-containing material as a polishing stop layer when polishing the oxide, and is also disadvantageous to shorten the time required for the polishing process.

[0083] The pH of the polishing composition of this embodiment is in the range of 1.5 or more and 4.5 or less. In such an environment, the surface zeta potential of the polishing abrasive grains is a positive value, and there is an electrostatic attraction between the polishing abrasive grains and the negatively charged object to be polished (e.g., oxide). Therefore, the polishing rate of the oxide can be increased. Furthermore, under acidic conditions, silica particles as polishing abrasive grains are unlikely to cause aggregation due to electrostatic repulsion, and the storage stability of the polishing composition can be significantly improved. More specifically, the pH of the polishing composition of this embodiment is preferably 1.8 or more, more preferably 2 or more, and even more preferably 2.5 or more. The pH of the polishing composition of this embodiment is preferably 4.2 or less, more preferably 4 or less, and even more preferably 3.5 or less.

[0084] In some embodiments, the polishing composition can have a pH of 1.5 or more, 1.6 or more, 1.7 or more, 1.8 or more, 1.9 or more, 2.0 or more, 2.1 or more, 2.2 or more, 2.3 or more, 2.4 or more, 2.5 or more, 2.6 or more, or 2.7 or more. Also, in some embodiments, the polishing composition can have a pH of 4.5 or less, 4.4 or less, 4.3 or less, 4.2 or less, 4.1 or less, 4.0 or less, 3.9 or less, 3.8 or less, 3.7 or less, 3.6 or less, or 3.5 or less.

[0085] If the pH value of the polishing composition is too high, the polishing rate of the oxide is significantly decreased, and the polishing rate ratio of the oxide to the silicon-containing material is also significantly decreased. Therefore, it is disadvantageous to use the silicon-containing material as a polishing stop layer when polishing the oxide, and is also disadvantageous to shorten the time required for the polishing process. Furthermore, if the pH value of the polishing composition is too high, the storage stability of the polishing composition may also be reduced. On the other hand, if the pH value of the polishing composition is too low, the safety of the process is reduced, and the burden of waste liquid treatment is increased.

[0086] [Dispersion medium] The polishing composition of this embodiment contains a dispersion medium (which may also be referred to as a "solvent"). The dispersion medium can be used to disperse or dissolve each component in the polishing composition. In this embodiment, the polishing composition may contain water as a dispersion medium. From the viewpoint of suppressing inhibition of the action of other components, water that contains as few impurities as possible is preferred. More specifically, pure water or ultrapure water that has been filtered to remove foreign matter after removing impurity ions with an ion exchange resin, or distilled water is preferred.

[0087] [Other ingredients] The polishing composition used in the polishing method of the present invention may further contain other components such as a chelating agent, an oxidizing agent, a metal corrosion inhibitor, an antiseptic, and an antifungal agent, if necessary.

[0088] [Polishing method and substrate manufacturing method] As described above, the polishing composition according to the present invention is particularly suitable for polishing a substrate containing a silicon-containing material and an oxide. Therefore, the present invention provides a polishing method for polishing an object to be polished containing a silicon-containing material and an oxide using the polishing composition according to the present invention. For example, the object to be polished may include a substrate made of a silicon-containing material and an oxide layer formed on the substrate. A specific example of the oxide is silicon oxide. A specific example of the silicon-containing material is a silicon-containing material having the molecular formula Si x Ge 1-x where x = 0.1 to 1. The present invention also provides a method for producing a substrate, comprising the step of polishing a substrate containing a silicon-containing material and a germanium oxide material using the polishing composition of the present invention.

[0089] When polishing a polishing object containing a silicon-containing material and an oxide, in order to use the silicon-containing material as a polishing stop layer during oxide polishing, the greater the difference between the removal rate of the oxide and the removal rate of the silicon-containing material, the better. In other words, the higher the polishing selectivity (polishing rate ratio or removal rate ratio) of the oxide to the silicon-containing material, the better. More specifically, when polishing a polishing object containing a silicon-containing material and an oxide at a specific polishing pressure (e.g., 1.0 psi), the ratio value (R1 / R2) of the removal rate R1 of the oxide to the removal rate R2 of the silicon-containing material is 10 or more, and the higher the ratio value R1 / R2, the better. In some embodiments of the present invention, when the polishing pressure is 1.0 psi, the removal rate of the polishing composition for the oxide is a first removal rate R1, the removal rate of the polishing composition for the silicon-containing material is a second removal rate R2, and the ratio value (R1 / R2) of the first removal rate to the second removal rate is preferably 10 or more, more preferably 15 or more, even more preferably 20 or more, and particularly preferably 30 or more. There is no particular upper limit to the ratio (R1 / R2) of the first removal rate to the second removal rate; the higher the better; however, for example, the ratio (R1 / R2) can be set to 200 or less.

[0090] The polishing apparatus used in the polishing step may be a polishing apparatus used in a general chemical mechanical polishing process. Such a polishing apparatus is equipped with a carrier for holding the object to be polished, a motor capable of changing the rotation speed, and the like, and also includes a polishing platen on which a polishing pad (or a polishing cloth) can be attached.

[0091] There is no particular limitation on the polishing pad, and it is possible to use a general nonwoven fabric, a polyurethane resin pad, a porous fluororesin pad, etc. Furthermore, if necessary, the polishing pad can be grooved, so that the polishing composition can be accumulated in the grooves of the polishing pad.

[0092] The parameter conditions of the polishing step are not particularly limited, and can be adjusted according to actual needs.For example, the rotation speed of the polishing platen can be 10 to 500 rpm, the rotation speed of the carrier can be 10 to 500 rpm, the flow rate of the polishing composition can be 10 to 500 mL / min, the polishing pressure can be 0.1 to 10 psi, and the polishing time can be 10 seconds to 30 minutes.The method of supplying the polishing composition to the polishing pad is also not particularly limited, and for example, a method of continuous supply using a pump or the like can be adopted.

[0093] After the polishing step is completed, the object to be polished is washed in a water stream and dried in a rotary dryer or the like to remove water droplets adhering to the object to be polished, thereby obtaining a substrate having a flat surface without any steps.

[0094] [Example] The present invention will be described in more detail with reference to the following examples and comparative examples, but the technical scope of the present invention is not limited to the following examples. In this specification, unless otherwise specified, operations and measurements of physical properties are performed under the conditions of room temperature (20 to 25°C) and relative humidity of 40 to 50% RH.

[0095] [Preparation of polishing composition] According to the composition shown in Table 1 below, polishing grains, additives and pH adjusters were mixed in a dispersion medium (ultrapure water) (mixing temperature: about 25°C, mixing time: about 10 minutes) to prepare a polishing composition. The pH of the polishing composition was confirmed with a pH meter (LAQUA manufactured by Horiba, Ltd.) (the temperature of the polishing composition during pH measurement was 25°C). In addition, "-" in Table 1 indicates that the component was not added. Details of each component in Tables 1 and 2 are as follows.

[0096] [Polishing grains and additive molecules] Abrasive grain a: colloidal silica (primary particle diameter: 30 nm, secondary particle diameter: 60 nm, silanol group density on the abrasive grain surface: 1.5 pieces / nm 2 ) Abrasive grain B: Colloidal silica (primary particle diameter: 35 nm, secondary particle diameter: 70 nm, silanol group density on the abrasive grain surface: 4.4 pieces / nm 2 ) Abrasive grain c: Colloidal silica (primary particle diameter: 35 nm, secondary particle diameter: 70 nm, silanol group density on the abrasive grain surface: 4.5 pieces / nm 2 ) Additive A: Glycerol (MW: 92 g / mol) Additive B: Polypropylene glycol 400 (MW: 446 g / mol) Additive C: Polyglycerin #310 (MW: 314g / mol) Additive D: Polyglycerin #500 (MW: 462 g / mol) Additive E: Polyglycerin #750 (MW: 759g / mol) Additive F: Polyglycerin 40 (MW: 2978 g / mol) Additive G: Polyglyceryl-4 lauryl ether (MW: 482 g / mol) Additive H: Polyglyceryl-10 lauric acid ester (MW: 940 g / mol) Additive I: Polyglyceryl-10 oleic acid ester (MW: 1022 g / mol) HNO3: Nitric acid (concentration: 70%) Additive J: Polyglyceryl-4 lauric acid ester (MW: 432 g / mol) Additive K: Polyglyceryl-6 lauric acid ester (MW: 548 g / mol) Additive L: Polytetrahydrofuran (=polytetramethylene ether glycol; MW: 250 g / mol).

[0097] The additive B is represented by the formula (I): 1 is H and R 2 C1~C 18 Straight chain alkyl group, C3-C 18 Branched chain alkyl group or C2-C 18 is a linear alkenyl group; n is an integer of 2 to 20; and m, p, q, and r are all 0. The additives C to F correspond to a compound in which R 1 and R 2 are both H; n is an integer of 2 to 40; and m and p are both 0, and q and r are 1. The additive G corresponds to a compound in which R 1 is C1~C 18 Straight chain alkyl group, C3-C 18 Branched chain alkyl group or C2-C 18 A linear alkenyl group, R 2 is H; n is an integer of 2 to 20; and m and p are both 0, and q and r are both 1. The additives H to K correspond to a compound in which R 1 is C1~C18 Straight chain alkyl group, C3-C 18 Branched chain alkyl group or C2-C 18 A linear alkenyl group, R 2 is H; n is an integer of 2 to 20; and m, q and r are all 1, and p is 0. The additive L corresponds to a compound represented by the formula (I) above, 1 and R 2 are all H; n is an integer from 2 to 20; and m, p and q are all 0, and r is 2.

[0098] [Measurement of secondary particle size of polishing abrasives] The average secondary particle diameter (unit: nm) of the polishing grains (colloidal silica) was measured as the volume average particle diameter (arithmetic mean diameter based on volume; Mv) for the polishing grain samples using a dynamic light scattering particle size distribution measuring device (manufactured by Nikkiso Co., Ltd.: UPA-UT151). The measurement results of the secondary particle diameter of the polishing grains are recorded in Tables 1 and 2.

[0099] [Measurement of surface zeta potential] The surface zeta potential of the polishing grains contained in the polishing composition was measured by a multiple frequency electro-acoustic method using an interface potential analyzer (Zeta Probe Analyzer manufactured by Colloidal Dynamics, Inc.). The measurement results of the surface zeta potential are recorded in Tables 1 and 2.

[0100] [Measurement of silanol group density on the surface of polishing abrasive grains] First, 1.50 g of colloidal silica as a solid content was weighed and placed in a 200 mL beaker, and about 100 mL of pure water was added to make a slurry, after which 30 g of sodium chloride was added and dissolved. Next, 1N hydrochloric acid was added to adjust the pH of the slurry to about 3.0 to 3.5, and then pure water was added to make the volume of the slurry 150 mL. This slurry was adjusted to pH 4.0 with 0.1N sodium hydroxide at 25°C using an automatic titration device (Hiranuma Sangyo Co., Ltd., COM-1700), and the volume V (unit: L) of the 0.1N sodium hydroxide solution required to increase the pH from 4.0 to 9.0 by pH titration was measured. The silanol group density on the surface of the polishing abrasive grains can be calculated by the following formula. The measurement results of the silanol group density on the surface of the polishing abrasive grains are recorded in the columns of polishing abrasive grains a to c in the details of each component ([polishing abrasive grains and additive molecules]) mentioned above.

[0101]

number

[0102] In the above formula, ρ is the density of silanol groups on the surface of the polishing grain (unit: silanol groups / nm 2 ) ; c represents the concentration of the sodium hydroxide solution used in the titration (unit: mol / L); V is the volume (unit: L) of sodium hydroxide solution required to increase the pH from 4.0 to 9.0; N A represents the Avogadro constant (unit: particles / mol); C represents the total mass (solid content) of silica (unit: g); S is the BET specific surface area of ​​silica (unit: nm 2 / g).

[0103] [Measurement of removal rate] The polishing composition obtained above was used to polish a silicon germanium (Si) plate with a diameter of 300 mm under the following conditions. x Ge 1-xThe removal rates were measured when polishing a 300 mm diameter silicon oxide (specifically, silicon oxide derived from tetraethyl orthosilicate (TEOS)) substrate (hereinafter abbreviated as "TEOS substrate"; manufacturer: Silicon Valley Microelectronic, Inc.; thickness: 10,000 Å) made of silicon dioxide (specifically, silicon dioxide derived from tetraethyl orthosilicate (TEOS)) substrate (manufacturer: Silicon Valley Microelectronic, Inc.; thickness: 10,000 Å). The removal rate measurements are shown in Tables 1 and 2.

[0104] Polishing equipment: Single-sided CMP polishing equipment (FREX 300E; manufactured by Ebara Corporation) Polishing pad: Polyurethane pad Plate rotation speed: 90 rpm Carrier rotation speed: 90 rpm Flow rate of polishing composition: 300 mL / min Polishing time: 60sec Grinding pressure: 1.0 psi (approximately 6.9 kPa).

[0105] The thickness of the polished object before and after polishing was measured using a film thickness measurement system (KLA-Tencor; ASET F5x). The removal rate was calculated using the following formula: Removal rate = {[Thickness before polishing] - [Thickness after polishing]} / [Processing time] In the above formula, the unit of thickness is Å, the unit of treatment time is minutes, and the unit of removal rate is (Å / min), where 1 Å=0.1 nm.

[0106] [Calculation of removal rate ratio value] The polishing step is performed at the above polishing pressure (i.e., 1.0 psi), and the removal rate R of the silicon germanium substrate at this polishing pressure is calculated by the above formula. SiGe , the removal rate of the polysilicon substrate R Si , the removal rate of silicon oxide substrate R TEOSThe removal rate R of the silicon oxide substrate at a polishing pressure of 1.0 psi was calculated. TEOS The removal rate of silicon germanium substrate R SiGe The ratio value (R TEOS / R SiGe ), the removal rate of silicon oxide substrate R TEOS The removal rate of the polysilicon substrate, R Si The ratio value (R TEOS / R Si ) was calculated. TEOS / R SiGe ) and (R TEOS / R Si ) can be used to represent the polishing selectivity of oxide to silicon-containing material at this particular polishing pressure (i.e., 1.0 psi). The higher the value of the removal rate ratio, the higher the polishing selectivity of oxide to silicon-containing material. The removal rate ratio values ​​(R TEOS / R SiGe ) and (R TEOS / R Si ) are also shown in Tables 1 and 2.

[0107] In this specification, the removal rate of the polishing composition for oxide is a first removal rate R1, and the first removal rate R1 is the removal rate R of the silicon oxide substrate in the example. TEOS and the removal rate of the polishing composition for the silicon-containing material is a second removal rate R2, and the second removal rate R2 corresponds to the removal rate R SiGe or the removal rate R of the polysilicon substrate Si It should be noted that the ratio value of the first removal rate to the second removal rate (R1 / R2) may correspond to the ratio value of the removal rate of the silicon oxide substrate to the removal rate of the silicon germanium substrate (R TEOS / R SiGe ) or the ratio of the removal rate of the silicon oxide substrate to the removal rate of the polysilicon substrate (R TEOS / R Si )

[0108] [Table 1]

[0109] [Table 2]

[0110] See Examples 1 to 8 in Table 1, Examples 11 to 13 in Table 2, and Comparative Example 1 in Table 1. Except that Comparative Example 1 does not use an additive having the structure represented by formula (I), the other experimental conditions of Examples 1 to 8, 11 to 13, and Comparative Example 1 are all the same or close to each other. From the experimental results, it can be seen that the removal rate ratio value (R TEOS / R SiGe ) and (R TEOS / R Si ) are 2.3 and 3.6, respectively, which means that both are less than 10. In comparison, all of Examples 1 to 8 use additives having the structure shown in formula (I) (i.e., additives B, C, D, E, F, G, H, and I), and the removal rate ratio values ​​(R TEOS / R SiGe ) and (R TEOS / R Si ) are all greater than 10. As can be seen from this, the polishing composition using the additive having the structure represented by formula (I) can significantly increase the polishing selectivity of TEOS to silicon germanium or silicon.

[0111] Please refer to Examples 1 to 8 in Table 1, Examples 11 to 13 in Table 2, and Comparative Example 2 in Table 1. Except that the additive used in Comparative Example 2 does not satisfy all the conditions of the structure represented by formula (I), the other experimental conditions in Examples 1 to 8, 11 to 13, and Comparative Example 2 are all the same or close. From the experimental results, it can be seen that the removal rate ratio value (R TEOS / R SiGe ) and (R TEOS / R Si) are 5.9 and 6.2, respectively, that is, both are less than 10. It should be noted that the additive used in the comparative example is glycerin (weight average molecular weight is 92), and the structure of glycerin is similar to the structure shown in formula (I), with the difference being that the chain segments of the main chain are relatively short, the hydrophilicity of the additive molecule is relatively strong, and the weight average molecular weight is also relatively small. As can be seen from this, even if the structure of the additive used is similar, if the weight average molecular weight of the additive molecule is too small or the hydrophilicity is too strong, the hydrophobic chain segments of the additive molecule will be too few, which is insufficient to effectively increase the polishing selectivity of TEOS to silicon germanium or silicon. In addition, the removal rate R of the TEOS substrate of Comparative Example 1 without the additive is 1.0 μm. TEOS (547 Å / min) compared to the removal rate R TEOS (533 Å / min) is rather low, which suggests that the use of additives may also result in a decrease in the oxide removal rate.

[0112] See Example 4 and Comparative Example 3 in Table 1. Except for the surface zeta potential of the polishing grain b used in Comparative Example 3 being a negative value (i.e., -132.0 mV), the other experimental conditions in Example 4 and Comparative Example 3 are all the same or close. From the experimental results, the removal rate ratio value (R TEOS / R SiGe ) and (R TEOS / R Si ) are 0.7 and 0.6, respectively, which is to say, both are much smaller than 10. In addition, in Comparative Example 3, the removal rate of the TEOS substrate was significantly decreased, so that the removal rate R TEOS (9Å / min) is the removal rate R of the silicon germanium substrate SiGe (13 Å / min) and the removal rate of the polysilicon substrate, R Si Note that the rate is smaller than (14 Å / min).

[0113] See Example 4 and Comparative Example 4 in Table 1. The silanol group density on the surface of the polishing abrasive grain c used in Comparative Example 4 was 4.5 / nm2 Except for this, the other experimental conditions of Example 4 and Comparative Example 4 are all the same or close to each other. From the experimental results, the removal rate ratio value (R TEOS / R SiGe ) and (R TEOS / R Si ) are 4.6 and 9.3, respectively, that is, both are less than 10. As can be seen from this, when polishing grains having an excessively high silanol group density are used, it is difficult to effectively increase the polishing selectivity of TEOS to silicon germanium or silicon. Furthermore, in Example 4 and Comparative Example 4, the removal rate R TEOS are 608 Å / min and 205 Å / min, respectively. In other words, the removal rates R TEOS However, the silanol group density in Comparative Example 4 is only about 1 / 3 of that in Example 4. As can be seen from this, if polishing grains with an excessively high silanol group density are used, the removal rate of the TEOS substrate is significantly reduced, which increases the time required for the polishing process.

[0114] Please refer to Examples 4, 9, 10 and Comparative Examples 5 and 6 in Table 1. Other than the pH of Examples 4, 9, 10 and Comparative Examples 5 and 6 being 2.0, 3.0, 4.0, 5.0, and 7.0, respectively, the other experimental conditions of Examples 4, 9, 10 and Comparative Examples 5 and 6 are all the same or close. It should be noted that although all of these use polishing grain a, the surface zeta potentials of the polishing grains of Comparative Examples 5 and 6 are all negative values ​​(-87.8 mV and -240.7 mV for Comparative Examples 5 and 6, respectively), while the surface zeta potentials of the polishing grains of Examples 4, 9, and 1 are all positive values ​​(36.7 mV, 33.9 mV, and 11.8 mV for Examples 4, 9, and 10, respectively). As can be seen from this, even if the same polishing grains are used, the surface zeta potentials of the polishing grains will also be different under different pH conditions. From the experimental results, the value of the removal rate ratio (R TEOS / R SiGe ) and (R TEOS / R Si ) were 0.5 and 0.4, respectively, and the removal rate ratio value (R TEOS / R SiGe) and (R TEOS / R Si ) are 1.0 and 0.9, respectively. That is, in Comparative Examples 5 and 6, the removal rate ratio values ​​(R TEOS / R SiGe ) and (R TEOS / R Si ) are both much smaller than 10. Furthermore, in Comparative Examples 5 and 6, the removal rate of the TEOS substrate is significantly decreased, so that the removal rate R TEOS (12 Å / min and 14 Å / min, respectively) are the removal rates R SiGe (26 Å / min and 14 Å / min, respectively) and the removal rate R of the polysilicon substrate Si (32 Å / min and 16 Å / min, respectively).

[0115] Please refer to Examples 1 to 10 in Table 1 and Examples 11 to 13 in Table 2. The polishing compositions used in Examples 1 to 10 each contain polishing grains (i.e., polishing grains a) that satisfy a specific range of silanol group density, and additives (i.e., additives B, C, D, E, F, G, H, I, J, K, and L) that satisfy all the conditions of the structure shown in the above formula (I), and the pH of the polishing composition satisfies the acidic range specified above (i.e., 2.0, 3.0, and 4.0). From the experimental results, the removal rate ratio values ​​(R TEOS / R SiGe ) and (R TEOS / R Si ) are all greater than 10. As can be seen from this, when a polishing composition in which an additive having a structure represented by formula (I) is combined with specific polishing grains under specific pH conditions is used, the polishing selectivity of TEOS to silicon germanium or silicon is significantly increased. In addition, the removal rate R TEOS (533 Å / min), the removal rate R TEOS(626 Å / min, 637 Å / min, 595 Å / min, 608 Å / min, 574 Å / min, 598 Å / min, respectively) all increased by more than 8%. This shows that by adjusting the type and content of additives, the oxide removal rate can be further increased and the time required for the polishing process can be shortened.

[0116] In summary, the polishing composition according to the present invention contains polishing grains that satisfy specific conditions and additives having a specific structure, and can significantly increase the polishing selectivity of oxides to silicon-containing materials in a specific pH environment. When a polishing object containing a silicon-containing material and an oxide is polished using the polishing composition according to the present invention, the silicon-containing material can be used as a polishing stop layer during oxide polishing. Therefore, the surface flatness of the polishing object can be improved, the complexity of the process can be simplified, and the time and cost required for production can be reduced. Furthermore, the polishing composition according to the present invention can adjust the removal rate of oxides by adjusting the type and content of additives. For example, the removal rate of oxides can be further increased, and the time required for the polishing process can be shortened.

[0117] Furthermore, the polishing composition of the present invention can be used in a chemical mechanical polishing process and is useful for obtaining a substrate having a flat surface, and thus has industrial applicability.

[0118] Although the present invention has been disclosed above by several preferred embodiments, these are not intended to limit the present invention, and those skilled in the art may of course make any changes and modifications without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention shall be determined by the following claims.

[0119] This application is based on the foreign language specification submitted accompanying the application of Japanese Patent Application No. 2019-209538 filed on November 20, 2019, the disclosure of which is incorporated herein by reference in its entirety.

Claims

1. 1. A polishing composition comprising: Abrasive grains containing silica particles, the silanol group density on the surface of the silica particles being 0 to 3.0 / nm 2 and The silanol density is calculated based on the specific surface area measured by the BET method and the amount of silanol groups measured by titration. an additive molecule having a structure as shown in formula (I); 【Chemistry 1】 (In formula (I), R 1 and R 2 are each independently H, C 1 ~C 18 Straight chain alkyl group, C 3 ~C 18 Branched alkyl group, or C 2 ~C 18 is a linear alkenyl group; n is an integer from 2 to 40; m, p, and q each independently represent 0 or 1; r represents an integer from 0 to 2; when m is 1, R 1 is C 1 ~C 18 Straight chain alkyl group, C 3 ~C 18 Branched alkyl group or C 2 ~C 18 is a linear alkenyl group, and when p is 1, R 2 is C 1 ~C 18 Straight chain alkyl group, C 3 ~C 18 Branched alkyl group or C 2 ~C 18 It is a linear alkenyl group. a pH adjuster for adjusting the pH of the polishing composition to a range of 1.5 or more and 4.5 or less; A dispersion medium; Including, A polishing composition for polishing an object to be polished, comprising an oxide and a silicon-containing material represented by Si x Ge 1-x (where x=0.1 to 1).

2. 2. The polishing composition according to claim 1, wherein the content of the additive molecules is 50 to 10,000 ppm by weight based on the total weight of the polishing composition.

3. 3. The polishing composition according to claim 1, wherein the weight average molecular weight of the additive molecule is 100 to 10,000.

4. In formula (I), R 1 is H, and R 2 C 1 ~C 18 Straight chain alkyl group, C 3 ~C 18 Branched alkyl group or C 2 ~C 18 is a linear alkenyl group; n is an integer from 2 to 20; and m, p, q and r are all 0; The polishing composition according to any one of claims 1 to 3.

5. In formula (I), R 1 and R 2 are all H; n is an integer from 2 to 40; and m and p are both 0, and q and r are both 1; The polishing composition according to any one of claims 1 to 3.

6. In formula (I), R 1 is C 1 ~C 18 Straight chain alkyl group, C 3 ~C 18 Branched alkyl group or C 2 ~C 18 is a linear alkenyl group, R 2 is H; n is an integer from 2 to 20; and m and p are both 0, and q and r are both 1; The polishing composition according to any one of claims 1 to 3.

7. In formula (I), R 1 is C 1 ~C 18 Straight chain alkyl group, C 3 ~C 18 Branched alkyl group or C 2 ~C 18 is a linear alkenyl group, R 2 is H; n is an integer from 2 to 20; and m, q and r are all 1, and p is 0; The polishing composition according to any one of claims 1 to 3.

8. In formula (I), R 1 and R 2 are all H; n is an integer from 2 to 20; and m, p and q are all 0, and r is 2; The polishing composition according to any one of claims 1 to 3.

9. 9. The polishing composition according to claim 1, wherein the content of the abrasive grains is 0.1 to 10 wt % based on the total weight of the polishing composition.

10. The method includes the step of polishing an object to be polished with the polishing composition according to any one of claims 1 to 9, wherein the material of the object to be polished includes an oxide and a silicon-containing material, and the silicon-containing material is Si x Ge 1-x and x=0.1 to 1.

11. 11. The polishing method according to claim 10, wherein when a polishing pressure is 1.0 psi, the polishing composition has a first removal rate R1 for the oxide, the polishing composition has a second removal rate R2 for the silicon-containing material, and a ratio value R1 / R2 of the first removal rate to the second removal rate is 10 or greater.

12. Providing a substrate, the surface of the substrate comprising an oxide and a silicon-containing material, the silicon-containing material being Si x Ge 1-x and x=0.1 to 1; polishing the substrate with the polishing composition according to any one of claims 1 to 9; A method for manufacturing a substrate comprising the steps of:

Citation Information

Patent Citations

  • Polishing composition, magnetic disk substrate manufacturing method and magnetic disk substrate

    JP2017019978A

  • Chemical mechanical polishing method for tungsten using polyglycol and polyglycol derivatives

    JP2018157195A

  • A process for the manufacture of semiconductor devices comprising the chemical mechanical polishing of elemental germanium and / or si1-xgex material in the presence of a CMP composition having a ph value of 3.0 to 5.5

    TW201311842A

  • Slurry and polishing method

    WO2018179064A1

  • Polishing solution and polishing method

    WO2019030865A1